65 Evaluation of Calcium to Phosphorus Ratio in Spot Urine Samples as a Practical Method to Monitor Phosphorus Intake Adequacy in Sows - Capdeville, Mariola Grez (J Anim Sci, 2021)
The reliability of spot urinary Ca to P ratio (uCa:P) to assess P intake adequacy in sows was evaluated. Thirty-six multiparous sows were fed one of six concentrations of dietary total P (0.40, 0.48, 0.56, 0.64, 0.72, and 0.80%), with a constant Ca to total P ratio (1.25:1), from day 7.5+1 after breeding until the end of lactation (day 26.6+1). Total 24-hour urine samples were collected in mid (day 77.1+2) and late gestation (day 112.4+1), and early (day 4.5+1 and late (day 18.2+1) lactation. In parallel to 24-hour collections, spot urine samples were collected at three times (early morning, late morning, and late afternoon) in late gestation and late lactation. Urine Ca and P concentrations were measured and uCa:P was calculated. Sows were classified as P-adequate or P-deficient according to dietary P intake. Sows fed P-deficient diets had greater uCa:P than sows fed P-adequate diets (P < 0.001). Receiver operator characteristic (ROC) curves were used to determine cut-off values for uCa:P to predict P intake adequacy. The area under the ROC for uCa:P was 0.88 (95% CI 0.81–0.95). Best cut-off value of uCa:P was 1.5 (sensitivity 94% and specificity 68%) to identify sows fed P-deficient diets, and 0.5 for P-excessive diets (sensitivity 82% and specificity 82%). A strong relationship between uCa:P in 24-hour and spot urine samples was determined (r = 0.93, P < 0.01), independent of physiological state and collection time of spot samples (adjusted-R(2) = 0.86, P < 0.01). The degree of agreement between spot and 24-hour urine for P intake adequacy, assessed by Cohen’s weighted kappa analysis, was substantial (0.78, 95% CI 0.69–0.88). Measurements of uCa:P in spot urine samples provide a reliable prediction of the adequacy of P intake in reproducing sows. Values of uCa:P > 1.5 were associated with P-deficient diets, whereas uCa:P < 0.5 reflected excessive P intake.